A bibliometric analysis of global scientific research output on Gum Arabic. (May 2021) - Musa, Taha H.; Musa, Idriss H.; Osman, Wadah; Campbell, Michael C.; Musa, Hassan H.
Abstract: Gum Arabic (GA) is an edible dried sticky exudate from the Acacia seyal and Acacia senegal trees (Fabaceae), which is widely used in the food and pharmaceutical industries. The goal of this study is to analyze the current state of research related to this important natural product. In total, 1411 publications, including 1393 data-driven and 18 review articles focused on GA, were identified from the Scopus database. We found that publications on GA were significantly increased globally after 2015. Moreover, the United States (U.S), India, and the United Kingdom (U.K.) are countries that have played a leading role in collaborative research on GA. Furthermore, our analyses revealed that Wrexham Glyndwr University, University of Edinburgh, and the University of Khartoum are currently the top producers of research. We also found that articles on GA were mainly published in Food hydrocolloids and Carbohydrate Polymers . Furthermore, G.O. Phillips, D.M.W. Anderson, and P.A. Williams were the most productive researchers on GA. In addition, our analyses revealed a significant correlation (r = 0.745, p < 0.01) between the total number of citations (TNC) and journal impact factor (IF), as well as a strong association between TNC and h-index (r = 0.891, P < 0.001) among published articles. Lastly, the U.S. had the highest influence among countries (TNC = 3646) followed by China (TNC = 3103). To date, a large increase in GA research has occurred in several countries outside of North America, Europe and Asia. However, this research activity in GA-producing countries is still in its infancy compared to other regions of the world. Highlights: A total of 1393 articles and 18 review papers indexed in Scopus database were associated with Gum Arabic (GA). GA publications were significantly increased after 2015. Food hydrocolloids and Carbohydrate Polymers were top journals published GA research.